Relationship between Mother's Knowledge and Status of Advanced Immunization Completeness in Children Under 2 Years in Karangpandan Community Health Center Working Area - Darsi, Darsi; Wijayanti, Wijayanti; Umarianti, Tresia (Journal of Advanced Nursing and Health Sciences, 2024)
Mother's knowledge about immunization influences the provision of immunization to babies. If the mother's knowledge about immunization is lacking and the mother feels that she does not need immunization, this will affect the schedule, administration and completeness of immunizations for babies, which will have an impact on the emergence of disease in babies. This research uses quantitative methods with a retrospective approach. The population of this research is all female orphans who are in the Karangpandan Health Center Working Area for the period March 2024, namely 44 toddler’s mom with the sampling technique used Total Sampling. The instruments used were a maternal knowledge questionnaire about advanced immunizations and a KIA book to see the completeness of immunization status. The statical test using Chi Square test results show the Asymp value. Sig. (2-sided) 0.001 < 0.05, meaning that Ha is accepted and Ho is rejected, so there is a relationship between the mother's level of knowledge about Advanced Immunization and the Completeness Status of Advanced Immunization for Children Under 2 Years in Karangpandan Community Health Center Working Area.